St. John's Wort for Major Depressive Disorder A Systematic Review - Ruelaz Maher, Alicia (RAND Corporation, 2015)
RAND researchers conducted a systematic review that synthesized evidence from randomized controlled trials of St. Johns wort-used adjunctively or as monotherapy-to provide estimates of its efficacy and safety in treating adults with major depressive disorder.